1950
DOI: 10.1113/jphysiol.1950.sp004494
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine synthesis in normal and denervated sympathetic ganglia of the cat

Abstract: MacIntosh (1938) was the first to relate the time of failure of conduction through a denervated sympathetic ganglion with a diminution in its acetylcholine content. From the work of Brown & Feldberg (1936) on perfused ganglia, and of Feldberg (1943) on incubated extracts of ganglia, it appeared that both events might be attributed to a failure of the preganglionic endings to synthesize acetylcholine. However, Feldberg's methods (1943) were relatively insensitive (Nachmansohn, John & Berman, 1946) and did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

1951
1951
1984
1984

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…In spite of their complexities the observations confirmed that at the time of failure of transmission a rapid functional break-down occurs in the nerve endings, associated with a decline in frequency and ultimate disappearance of the spontaneous potentials. (MacIntosh, 1938;Lissak, Dempsey & Rosenblueth, 1939;Feldberg, 1943;Banister & Scrase, 1950), namely that failure of transmission at a degenerating synapse is associated with a stoppage of transmitter production and therefore also with disappearance of the spontaneous miniature potentials (Fatt & Katz, 1952;Liley, 1956a). On further exploration, however, we found that spontaneous subthreshold activity was resumed at the denervated end-plates during the course of the second week.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…In spite of their complexities the observations confirmed that at the time of failure of transmission a rapid functional break-down occurs in the nerve endings, associated with a decline in frequency and ultimate disappearance of the spontaneous potentials. (MacIntosh, 1938;Lissak, Dempsey & Rosenblueth, 1939;Feldberg, 1943;Banister & Scrase, 1950), namely that failure of transmission at a degenerating synapse is associated with a stoppage of transmitter production and therefore also with disappearance of the spontaneous miniature potentials (Fatt & Katz, 1952;Liley, 1956a). On further exploration, however, we found that spontaneous subthreshold activity was resumed at the denervated end-plates during the course of the second week.…”
Section: Resultsmentioning
confidence: 70%
“…In sympathetic ganglia, it has been shown that ACh synthesis vanishes within a short time after preganglionic nerve section (Feldberg, 1943;Banister & Scrase, 1950; see also Brown & Feldberg, 1936;MacIntosh, 1938). This does not necessarily conflict with our interpretation; for it would be impossible to say whether the production of ACh is completely abolished or persists at a level of less than 1% of the initial rate, and no more than this would be required to maintain the renewed end-plate activity.…”
Section: Discussionmentioning
confidence: 99%
“…Functional and structural changes have been described at the amphibian neuromuscular junction only after 3 days denervation (Birks, Katz & Miledi, 1960). For cat superior cervical ganglion, decline of acetylcholine content has been noted within 30 hr after preganglionic section (Banister & Scrase, 1950). Emmelin (1962) did not observe 'paralytic secretion' by the cat submaxillary gland until 14 hr or longer after post-ganglionic denervation.…”
Section: Discussionmentioning
confidence: 99%
“…As this output per minute represents the rate of synthesis of transmitter at the time when the steady level of release is reached, the rate of synthesis must also be proportional to the frequency of stimulation. The rates of ACh synthesis observed in intact nervous tissue (Banister & Scrase, 1950;Hebb, Krnjevfc & Silver, 1964) are well below the rates dictated by the activity of the enzyme or the concentration of the substrate (Potter, Glover & Saelens 1968). There is only limited inhibition of choline acetyltransferase by ACh at concentrations approaching those which probably occur in the nerve terminals (Kaita & Goldberg, 1969;Glover & Potter, 1971 A model of the storage and synthesis of ACh in preganglionic terminals, derived from the results of the electrophysiological experiments reported in this and the preceding paper (Bennett & McLachlan, 1972) impulses.…”
Section: Discussionmentioning
confidence: 99%